Longitudinal monitoring of disease burden and response using ctDNA from dried blood spots in xenograft models - Carolin M Sauer; Katrin Heider; Jelena Belic; Samantha E Boyle; James A Hall; Dominique‐Laurent Couturier; Angela An; Aadhitthya Vijayaraghavan; Marika AV Reinius; Karen Hosking; Maria Vias; Nitzan Rosenfeld; et al. (EMBO Molecular Medicine)
Abstract Whole‐genome sequencing (WGS) of circulating tumour DNA (ctDNA) is now a clinically important biomarker for predicting therapy response, disease burden and disease progression. However, the translation of ctDNA monitoring into vital preclinical PDX models has not been possible owing to low circulating blood volumes in small rodents. Here, we describe the longitudinal detection and monitoring of ctDNA from minute volumes of blood in PDX mice. We developed a xenograft Tumour Fraction (xTF) metric using shallow WGS of dried blood spots (DBS), and demonstrate its application to quantify disease burden, monitor treatment response and predict disease outcome in a preclinical study of PDX mice. Further, we show how our DBS‐based ctDNA assay can be used to detect gene‐specific copy number changes and examine the copy number landscape over time. Use of sequential DBS ctDNA assays could transform future trial designs in both mice and patients by enabling increased sampling and molecular monitoring.